Persuasão em propagandas sociais multimodais do governo do Maranhão na temática da vacinação da COVID-19: um enfoque da linguística sistêmico-funcional - Pereira, Denise Maia (2024)
Multimodal social advertisings have a significant role into molding public opinion about social and political questions. In studies of persuasive power, the language of these texts have been the focus to a certain extent, since writing, previously the canonical mode for excellence, is becoming associated with images, constituting what has been called multimodality. In this context, it is observed that persuasion tends to be highly implicit and avoid the attitudinal language normally associated with interpersonal meaning, depending largely, for example, on shared value system (frame). It is what happens with conceptual metaphor, which always involves a degree of perspective, when certain features are highlighted while others remain obscured. Related to the question, conceptual metonymy, thanks to its indexical character, is a cognitive process that via frame allows the addressee to infer the implicit content of the message through verbal-visual clues and the communication context. The functional view of Systemic Functional Linguistics (SFL) offers a specific analytical instrument to the systematic examination of the motivations, purposes, suppositions, and interest of the text producer. Reading the underlying text also has the support of Visual Design Grammar. The objective of this doctoral thesis is to examine the persuasive function, both explicit and implicit, and its occurrence in social propaganda focused on the topic of COVID-19, on the official profile of the government of the State of Maranhão, on a social network. This thesis answers the following questions: (a) how is implicit persuasion carried out in multimodal social propaganda? (b) what is the role of metonymy and metaphor in the process? (c) what’s the contribution of Systemic Functional Linguistics to the examination carried out in (a) and (b). The results show that implicit persuasion is carried out with the support of appraisal and transitivity resources, the images not only but also complement the verbal meaning of the persuasive process through metaphor, with the contribution of metonymy, which helps in the understanding of social advertising, thanks to its power to evoke the message via frame to the reader